IMPACT OF 3/4th SUBLETHAL CONCENTRATION OF CYPERMETHRIN ON HAEMATOLOGICAL PARAMETERS OF FISH, CHANNA MARULIUS (HAM. BUCH). - BHOI, S.S.; PATIL, M.U.; PATOLE, S.S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2016)
The present investigation was carried out to investigate the effect of Cypermethrin on haematological parameters in freshwater fish, Channa marulius (Ham. Buch) using standard methods. Fish were exposed to 3/4" sub lethal concentration i.e. 0.18 ppm for 96 h. The control and experimental fish were assayed for haematological parameters viz. Total erythrocytes count (TEC), Total leucocytes count (TLC), Haemoglobin (Hb), Packed cell volume (PCV), Mean Corpuscular Volume (MCV) and Mean corpuscular haemoglobin concentration (MCHC). The result revealed that, TEC, Hb% and PCV counts were significantly decreased. Whereas TLC, MCV and MCH was slightly increased and the MCHC count of experimental fish decreased. The study has, thus, indicated marked changes in blood of Channa marulius after exposure to Cypermethrin.